2012
DOI: 10.1007/s10059-012-2217-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autoproteolytic Cleavage of mCLCA6, a Murine Integral Membrane Protein Expressed in Enterocytes, Leads to Cleavage at the Plasma Membrane Instead of the Endoplasmic Reticulum

Abstract: CLCA proteins (calcium-activated chloride channel regulators) have been linked to diseases involving secretory disorders, including cystic fibrosis (CF) and asthma. They have been shown to modulate endogenous chloride conductance, possibly by acting as metalloproteases. Based on the differential processing of the subunits after posttranslational cleavage, two subgroups of CLCA proteins can be distinguished. In one subgroup, both subunits are secreted, in the other group, the carboxy-terminal subunit possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Moreover, subsequent findings were more consistent with the proposal that CLCA1 effects on chloride transport may be based on increasing conductance of endogenous CaCCs (40). It further appears (based on analysis of crude membrane preparations) that secreted CLCA proteins are first processed intracellularly into N-terminal and C-terminal peptide fragments (18,39,(41)(42)(43)(44). The present findings support this alternative proposal as well, in that CLCA1 is colocalized within the cell along with MUC5AC in secretory granules and is secreted to the apical cell surface in response to IL-13.…”
Section: Figuresupporting
confidence: 77%
“…Moreover, subsequent findings were more consistent with the proposal that CLCA1 effects on chloride transport may be based on increasing conductance of endogenous CaCCs (40). It further appears (based on analysis of crude membrane preparations) that secreted CLCA proteins are first processed intracellularly into N-terminal and C-terminal peptide fragments (18,39,(41)(42)(43)(44). The present findings support this alternative proposal as well, in that CLCA1 is colocalized within the cell along with MUC5AC in secretory granules and is secreted to the apical cell surface in response to IL-13.…”
Section: Figuresupporting
confidence: 77%
“…First, we have demonstrated that CLCA proteins represent a novel class of zincin metalloproteases capable of self-and crosscleavage. It should be noted that previous studies have attempted to address the issue of CLCA metalloprotease activity (28,29); however, these studies were based on experiments utilizing CLCA proteins found in crude membrane fractions. The authors claimed that purified CLCA proteins could not be produced.…”
Section: Discussionmentioning
confidence: 99%
“…3C). Previous studies have reported that mutations of Glu-157 in human CLCA1 (24), murine CLCA3 (28), and murine CLCA6 (29) to Gln all produce mutant proteins that are not proteolytically processed. However, the significance of these results is difficult to interpret as these studies probed the protein from crude cell lysates.…”
Section: Proteolytic Processing Of Clca Requires Catalytic Residues Imentioning
confidence: 99%
“…It has furthermore been argued, based on bioinformatics analysis, that CLCAs have autoproteolytic activity at a specific domain and similar results have frequently been reported in more recent studies (Pawlowski et al 2006;Yurtsever et al 2012). For example, mCLCA3 and mCLCA6 have been found to have self-cleavage activity dependent on the HExxH domain and in a study on hCLCA1, proteins were purified and registered to the enzyme database as metalloendopeptidases (metalloprotease) (Bothe et al 2011(Bothe et al , 2012Yurtsever et al 2012).…”
Section: Introductionmentioning
confidence: 77%
“…To this end, most research on CLCAs has been focused largely on the electrophysiological function of these proteins; however, the more CLCA research goes on, the more intriguing questions have come out (Mundhenk et al 2012;Pawlowski et al 2006;Song et al 2009;Yurtsever et al 2012). Among several established properties, CLCAs have more recently been proven to contain less transmembrane (TM) domains than previously thought, or even no TM domains at all Gibson et al 2005).…”
Section: Introductionmentioning
confidence: 98%